Genome-Wide Analysis and Expression Profiling of Watermelon VQ Motif-Containing Genes Under Abiotic and Biotic Stresses - Yanjun He; Jia Shen; Xinyang Xu; Weisong Shou (Horticulturae)
Valine-glutamine (VQ) motif-containing proteins play important roles in diverse plant developmental processes and signal transduction in response to biotic and abiotic stresses. However, no systematic investigation has been conducted on VQ genes in watermelon. In this study, we identified 31 watermelon VQ genes, which were classified into six subfamilies (I–VI). All of the deduced proteins contained a conserved FxxxVQxL/F/VTG motif. Eleven ClVQs were involved in segment duplication, which was the main factor in the expansion of the VQ family in watermelon. Numerous stress- and hormone-responsive cis-elements were detected in the putative promoter region of the ClVQ genes. Green fluorescent protein fusion proteins for ten selected ClVQs were localized in the nucleus, but three ClVQs also showed signals in cell membranes and the cell wall, thus confirming their predicted divergent functionality. Quantitative real-time PCR (qRT-PCR) analysis indicated that the majority of ClVQ genes were specifically or preferentially expressed in certain tissues or organs, especially in the male flower. Analyses of RNA-sequencing data under osmotic, cold, and drought stresses and Cucumber green mottle mosaic virus (CGMMV) infection revealed that the majority of ClVQ genes, especially those from subfamily IV, were responsive to these stresses. The results provide useful information for the functional characterization of watermelon ClVQ genes to unravel their biological roles.